STUDI KEANDALAN POTENSI PEMANFAATAN AIR HUJAN SEBAGAI SUMBER AIR BERSIH DI LINGKUNGAN UNIVERSITAS PANCA BHAKTI, KOTA PONTIANAK - gunawan, ivan andri; Anggraini, Ika Muthya; Widodo, Muji Listyo (Jurnal Teknologi Infrastruktur, 2024)
The high rainfall in Pontianak provides a great opportunity to utilize rainwater as a source of clean water in the area. This study aims to analyze the potential for utilizing rainwater in the Panca Bhakti University environment from the aspects of reliability and volume of water that can be accommodated. The study was conducted through a quantitative method by measuring the roof area, and collecting rainfall data from secondary data, as well as simulating the calculation of the volume of water that can be accommodated from the roof of the campus building. The results of the study showed that the roof area of ​​the building in the Panca Bhakti University area is 1,508.99 m2. From the roof area, the calculation results show that the potential volume of rainwater that can be accommodated is 282,181.13 liters / month or 11,757 liters / day. The total need for clean water use in the Panca Bhakti University environment is 69,926 liters / day. The percentage of rainwater capacity from the total daily clean water use requirement is 16.814%. From the results of this calculation, we can conclude that in terms of reliability, rainwater has not been able to meet the clean water needs in the Panca Bhaktit University Area as a whole. However, if we integrate it with the use of PDAM water, rainwater has great potential to meet the campus's water needs, especially in reducing the cost of PDAM water usage bills, especially in daily activities that do not require drinking quality water, as well as contributing to groundwater conservation and reducing environmental impacts. Keywords: Rain Water, Rain Water Harvesting, Water Quality, Water Conservation